Combustion and Emission Characteristics of CNG-Diesel Dual Fuel Engine with Variation of Air Fuel Ratio - Dori Yuvenda; Bambang Sudarmanta; Jamaludin Jamaludin; Oki Muraza; Randi Purnama Putra; Remon Lapisa; Krismadinata Krismadinata; Rahadian Zainul; Asnil Asnil; Muji Setiyo; Sri Rizki Putri Primandari (Universitas Muhammadiyah Magelang, 2022)
Compressed natural gas (CNG) is a popular alternative fuel because of its more environmentally friendly properties than fossil fuels , including applications in diesel engines. However, supplying too much compressed natural gas fuel causes poor engine performance and emissions due to a decrease in the air-fuel ratio on the dual-fuel engine. The addition of air using electric superchargers was done to return the air-fuel ratio to ideal conditions. Lambda value (Î») was variation under low load (1.52 to 2.71), medium load (1.18 to 2.17), and high load (0.94 to 2.17) on a CNG-diesel dual fuel engine. The addition of pure air in each load can increase combustion stability in certain lambda, which was indicated by an increase in thermal efficiency, heat release rate, and a decrease in ignition delay, combustion duration, hydrocarbon, and carbon monoxide emissions.